The Role of Religious Teachers in Preventing Verbal Bullying in Islamic Vocational High Schools - Sapriadi Manik; Muhammad Anas Ma’arif (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study explores the role of religious teachers in preventing verbal bullying at SMKS Mahyal Ulum Al-Aziziyah. The research is motivated by the increasing number of bullying cases in schools, which negatively affect students’ character and psychological development. The study aims to describe the role of religious teachers in preventing verbal bullying, identify the types of bullying that occur, and analyze the supporting and inhibiting factors of prevention efforts. This research employs a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed descriptively. The findings show that verbal bullying still occurs in the form of teasing, mocking, gossiping, and humiliating nicknames. Religious teachers play an essential role through personal approaches, Islamic value inculcation, advice, and religious character formation. The main supporting factors are the principal’s support and the school’s religious culture, while the inhibiting factors include lack of parental attention and limited teacher supervision outside class hours. The study concludes that the role of religious teachers is strategic in fostering a safe, ethical, and Islamic school environment.